Study of Antibacterial Activity of Root Bark, Leaves, and Pericarp Extracts of Diploknema butyracea and Evaluation of Prospective Antioxidant Activity. (23rd March 2022) - Chhetry, Alisha Karki; Dhakal, Subhila; Chaudhary, Lalita; Karki, Khimdhoj; Khadka, Ram Bahadur; Chaudhary, Gautam Prasad; Bastola, Tonking; Poudel, Amrit; Aryal, Pramod; Pandey, Jitendra
Abstract : This study was aimed to determine the antibacterial activity of root bark, leaves, and pericarp extract of Diploknema butyracea and to evaluate the prospective antioxidant activity, total flavonoid, polyphenol, and carbohydrate content. The plant parts were collected and extracted by cold maceration, using hexane, ethyl acetate, methanol, and distilled water. Phytochemical screening of different samples of D. butyracea in different solvents revealed the presence of varied extent of alkaloid, saponin, terpenoid, anthraquinones, tannin, cardiac glycoside, flavonoid, carbohydrate, polyphenol, protein and amino acid, resin, and phytosterol. Our study showed that methanolic root bark extract exhibited the potent antimicrobial activity against Staphylococcus aureus, Staphylococcus epidermidis, and Klebsiella pneumonia with an average zone of inhibition of 17.33 mm, 14.33 mm, and 13.0 mm, respectively. Surprisingly, all of the extracts were insensitive to Escherichia coli . The lowest minimum bactericidal concentration (MBC), 4.6 mg/ml, was observed with the aqueous pericarp extract against S. epidermidis and the highest was of 50 mg/ml shown by ethyl acetate pericarp against K. pneumonia . Our results showed that both the polar and nonpolar components present in the different parts of D. butyracea exhibit prominent antibacterial activities against different bacterial strains. The in vitro 2, 2′-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity showed that the methanol extract of root barks displayed the most potent antioxidant activity (IC50  : 6.1  µ g/ml). The total polyphenol content of the plant part extracts was observed between 19.48 ± 0.23 and 123.48 ± 1.84  µ g gallic acid equivalent/mg of dry extract weight. Likewise, flavonoid content ranged from 40.63 ± 1.28  µ g to 889.72 ± 3.40  μ g quercetin equivalent/mg of dry extract weight and total carbohydrate content ranged from 11.92 ± 0.60  µ g to 174.72 ± 0.60  µ g glucose equivalent per/mg dry extract weight. Overall, our study showed that the root bark, pericarp, and leaves extract of D. butyracea evinced prominent antibacterial properties against various pathogenic bacterial strains.